Listening: Beyond Telling to “Being” What We Want To Teach - Roben Torosyan (Journal of the Assembly for Expanded Perspectives on Learning, 2004)
In response to a culture of polarized argument, this paper shows a way to provide people with practice at deep listening and understanding. The author examines ways in which self-disclosure about problems of dialog may be an ideal means for teachers or leaders to show people alternate ways of being in the world of meaning making.